Application of three-dimensional culture conditions to human embryonic stem cell-derived definitive endoderm cells enhances hepatocyte differentiation and functionality - Ramasamy, T.S.; Yu, J.S.L.; Selden, C.; Hodgson, H.; Cui, W. (2013)
Human embryonic stemcells (hESCs) and induced pluripotent stemcells (iPSCs) provide an unlimited source for the generation of human hepatocytes, owing to their indefinite self-renewal and pluripotent properties. Both hESC-/iPSC-derived hepatocytes hold great promise in treating liver diseases as potential candidates for cell replacement therapies or as an in vitro platform to conduct newdrug trials. It has been previously demonstrated that the initiation of hESC differentiation in monolayer cultures increases the generation of definitive endoderm (DE) and subsequently of hepatocyte differentiation. However, monolayer culture may hinder the maturation of hESC-derived hepatocytes, since such two-dimensional (2D) conditions do not accurately reflect the complex nature of three-dimensional (3D) hepatocyte specification in vivo. Here, we report the sequential application of 2D and 3D culture systems to differentiate hESCs to hepatocytes. Human ESCs were initially differentiated in a monolayer culture to DE cells, which were then inoculated into Algimatrix scaffolds. Treatments of hESC-DE cells with a ROCK inhibitor before and after inoculation dramatically enhanced their survival and the formation of spheroids, which are distinct from HepG2 carcinoma cells. In comparison with monolayer culture alone, sequential 2D and 3D cultures significantly improved hepatocyte differentiation and function. Our results demonstrate that hESC-DE cells can be incorporated into Algimatrix 3D culture systems to enhance hepatocyte differentiation and function.